Metsamor. Reconstruction of urban space arrangement and its significance - Jakubiak , Krzysztof (ARAMAZD: Armenian Journal of Near Eastern Studies, 2025)
The remains of a small town that was active on the Ararat Plain during the Early Iron Age have been uncovered during recent excavations at Metsamor. The character of the recently cleaned architectural remains raises questions about the city’s nature during the period when the first proto-state political organisms were active. The distribution of the dwellings, the arrangement of the internal spaces and the remains of monumental architecture all suggest that this small town may have played a more important role than has been previously thought. Of particular importance from the point of view of the text below will be the changes in the structure of the town over the centuries. The layout and use of the site during the first centuries AD. deserve special attention. Promising results have been obtained which should serve as a starting point for analysis. This analysis should focus not only on the study of the architectural remains but also on other artefacts and evidence uncovered during the excavations. Therefore, all of the data collected should be examined from a broader perspective when looking at the Metsamor site. It is important to note that few traces of other archaeological sites remain in the vicinity of the town. The character of the town, its dynamic changes and the activities carried out by the local communities who once lived in Metsamor are fascinating but can be studied.